Waste management in the production dairy industry - C. Fulhage (Kansas Agricultural Experiment Station Research Reports, 1992)
The impact of environmental regulation on livestock production enterprises is, inevitably, an increase in production costs. Producers should recognize that these are the costs of doing business and will probably have to be incurred by all producers who stay in business and remain viable. With proper input to the regulation process and implementation of practical and effective methods of manure management, most producers should be able to maintain viable enterprises.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Waste management; Production dairy indistry; Dairy